PENYIDIKAN TINDAK PIDANA MENGEDARKAN UANG PALSU PADA SATUAN RESERSE KRIMINAL (SATRESKRIM) POLRES AGAM - Sembiring, Susanti; Sembiring, Tuti Kelana; Satriadi, Efendi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The investigation into criminal acts of counterfeit money by the Agam Resort Police is an effort to enforce the law against the circulation of counterfeit money, where the perpetrator circulates counterfeit money in the market using a small shopping mode to receive real money back. Based on public reports, the police followed up on this case by arresting the perpetrator and confiscating evidence of counterfeit money. In practice, these investigations face limited resources and equipment. Juridically, the perpetrator's actions violated Article 36 of Law Number 7 of 2011 concerning Currency and Article 244 of the Criminal Code which carries a criminal penalty of up to 15 years in prison. It is hoped that this law enforcement effort will be able to provide a deterrent effect and increase public trust in the police in tackling economic crime. Keywords: Investigation, Crime, Counterfeit Money, Religion.